Pengaruh Leverage, Likuiditas, dan Profitabilitas Terhadap Nilai Perusahaan Pada Sub Sektor Hotel, Restoran, dan Pariwisata - Putri, Kesya Nadya Gita; Prasetio, Januar Eko (Equity: Jurnal Akuntansi, 2024)
The aim of this research is to determine the effect of leverage, liquidity and profitability on company value. The population in this research is hotels, restaurants and tourism sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. The samples obtained were 120 companies using purposive sampling. The analysis technique used in this research is multiple linear regression analysis. The data was processed using the IBM SPSS Statistics 25 application. The results of this research show that leverage has an effect on company value. Meanwhile, liquidity and profitability have no effect on company value.